Intrauterine adhesion in ultrasound-guided manual vacuum aspiration (USG-MVA) versus electric vacuum aspiration (EVA): a randomised controlled trial - Jacqueline Pui Wah Chung; Tracy Sze Man Law; Karen NG; Patricia Nga Ping IP; Tin Chiu Li (BMC, 2024)
Abstract Background Intrauterine adhesion (IUA) can arise as a potential complication following uterine surgery, as the surgical procedure may damage the endometrial stratum basalis. The objective of this study was to assess and compare the occurrence of IUA in women who underwent ultrasound-guided manual vacuum aspiration (USG-MVA) versus electric vacuum aspiration (EVA) for managing first-trimester miscarriage. Methods This was a prospective, single-centre, randomised controlled trial conducted at a university-affiliated tertiary hospital. Chinese women aged 18 years and above who had a delayed or incomplete miscarriage of ≤ 12 weeks of gestation were recruited in the Department of Obstetrics and Gynaecology at the Prince of Wales. Recruited participants received either USG-MVA or EVA for the management of their miscarriage and were invited for a hysteroscopic assessment to evaluate the incidence of IUA between 6 and 20 weeks after the surgery. Patients were contacted by phone at 6 months to assess their menstrual and reproductive outcomes. Results 303 patients underwent USG-MVA or EVA, of whom 152 were randomised to 'USG-MVA' and 151 patients to the 'EVA' group. Out of the USG-MVA group, 126 patients returned and completed the hysteroscopic assessment, while in the EVA group, 125 patients did the same. The incidence of intrauterine adhesion (IUA) was 19.0% (24/126) in the USG-MVA group and 32.0% (40/125) in the EVA group, showing a significant difference (p < 0.02) between the two groups. No significant difference in the menstrual outcomes at 6 months postoperatively between the two groups but more patients had miscarriages in the EVA group with IUA. Conclusions IUAs are a possible complication of USG-MVA. However, USG-MVA is associated with a lower incidence of IUA postoperatively at 6-20 weeks. USG-MVA is a feasible, effective, and safe alternative surgical treatment with less IUA for the management of first-trimester miscarriage. Trial registration The study was registered with the Centre for Clinical Research and Biostatics- Clinical Trials Registry (CCRBCTR), which is a partner registry of the WHO Primary Registry-Chinese Clinical Trials Registry (ChiCTR) (Unique Trial Number: ChiCTR1900023198 with the first trial registration date on 16/05/2019)